Introduction to flight - Anderson, John David (McGraw-Hill Higher Education, 2005)
Noted for its highly readable style, the new edition of this bestseller provides an updated overview of aeronautical and aerospace engineering. Introduction to Flight blends history and biography with discussion of engineering concepts, and shows the development of flight through this perspective. This edition covers new developments in flight, including unmanned aerial vehicles, uninhabited combat aerial vehicles, and applications of CFD in aircraft design